Offshoring and job stability: Evidence from Italian manufacturing - Alessia Lo Turco; Daniela Maggioni; Matteo Picchio (Institute for the Study of Labor (IZA), 2012)
We study the relationship between offshoring and job stability in Italy in the period 1995-2001 by using an administrative dataset on manufacturing workers. We find that the international fragmentation of production negatively affects job stability. Service offshoring and material purchases from developed countries foster job-to-job transitions within manufacturing of all workers and white collars, respectively. However, the most detrimental effects for job stability come from material offshoring to low income countries which drives blue collar workers out of manufacturing. Therefore, policy interventions should especially focus on this latter category of workers more exposed to fragmentation processes and foreign competition.
urn:nbn:de:101:1-201208096329
Keywords: C41; F14; F16; J62; 330; offshoring; job stability; manufacturing; duration analysis; proportional hazard; Auslandsverlagerung; Beschäftigungseffekt; Verarbeitendes Gewerbe; Italien